Comparisons Between Normobaric Normoxic and Hypoxic Recovery on Post-exercise Hemodynamics After Sprint Interval Cycling in Hypoxia - Horiuchi, Masahiro; Nishida, Ayano; Dobashi, Shohei; Koyama, Katsuhiro (Frontiers in Physiology, 2022)
The aim of this study was to investigate the effects of either normoxic or hypoxic recovery condition on post-exercise hemodynamics after sprint interval leg cycling exercise rather than hemodynamics during exercise. The participants performed five sets of leg cycling with a maximal effort (30 seconds exercise for each set) with a 4-min recovery of unloaded cycling between the sets in hypoxia (fraction of inspired oxygen [FiO2]=0.145). The load during pedaling corresponded to 7.5% of the individual’s body weight at the first set, and it gradually reduced from 6.5% to 5.5%, 4.5%, and 3.5% for the second to fifth sets. After exercise, the participants rested in a sitting position for 30 minutes under normoxia (room-air) or hypoxia. Mean arterial pressure decreased over time during recovery (P< 0.001) with no condition and interaction effects (P>0.05). Compared to pre-exercise values, at 30 minutes after exercise, mean arterial pressure decreased by 5.6±4.8 mmHg (mean±standard deviation) during hypoxic recovery, and by 5.3±4.6 mmHg during normoxic recovery. Peripheral arterial oxygen saturation (SpO2) at all time points (5, 10, 20, and 30 minutes) during hypoxic recovery was lower than during normoxic recovery (all P<0.05). The area under the hyperemic curve of tissue oxygen saturation (StO2) at vastus lateralis defined as reperfusion curve above the baseline values during hypoxic recovery was lower than during normoxic recovery (P<0.05). Collectively, post-exercise hypotension after sprint interval leg cycling exercise was not affected by either normoxic or hypoxic recovery despite marked differences in SpO2 and StO2 during recovery between the two conditions.